BUSINESS SUBJECT STUDENTS’ PERCEIVED BENEFITS OF UTILIZATION OF LIBRARY RESOURCES IN SECONDARY SCHOOLS IN OGIDI ZONE, ANAMBRA STATE (NAU Journal of Technology and Vocational Education, 2024)
The need to encourage students’ utilization of library resources for better academicperformance necessitated this study. The study ascertained the benefit of utilizationof library resources as perceived by business subjects’ students in secondaryschools in Ogidi zone, Anambra State. Descriptive survey research design wasadopted for the study. The population consisted of 3577 business subject studentsand a sample size of 520was drawn for the study using stratified random samplingtechniqueOne research question guided the study and two null hypotheses weretested. An 11- item structured questionnaire validated by three experts was used fordata collection. The reliability of the instrument was established using test re-testmethod and data analyzed using Pearson Product Moment Correlation Coefficient;this yielded reliability coefficient of 0.83. Data were analyzed using mean andstandard deviation to answer the research question and to determine the closenessof the respondent’s means, while z-test was used to test the null hypotheses at 0.05level of significance. The results revealed that business subject students insecondary schools in Ogidi zone, Anambra State agreed that library resources helpstudents to use and cite materials accurately. The students strongly agree thatlibrary resources offer an environment that is conducive for study. It was found thatthe business subject students did not differ significantly on their mean responses onthe benefit of utilization of library resources in secondary schools based on genderand location of the school libraries. It was recommended among others thatmanagement of secondary schools in Anambra State should organize seminars andworkshop programs to enlighten student on the relevant and the use of libraryresources. This will help in enhancing the usage of library resources amongstudents and improve their academic performance.